Screening for congenital heart disease prior to fetal surgery - Gil Guevara, Enrique (2024)
Congenital cardiopathies are the most frequent malformations and represent ahigh neonatal morbidity and mortality rate, especially in those neonates withouttimely prenatal diagnosis. They appear as the first cause of infant death associatedwith congenital malformations. Advances in technology and the standardization ofultrasound diagnostic protocols have allowed increasingly accurate identificationof congenital heart diseases. However, this has not been sufficient and therecontinues to be a high rate of neonates with congenital heart disease undiagnosedin prenatal surveillance. On the other hand, with the advent of fetal surgery, it isnecessary to identify the presence of any major congenital heart disease thatcould cloud the prognosis associated with the underlying fetal pathology thatmade intrauterine intervention necessary. Considering the above, both parentsand medical professionals need to be made aware of the importance of screeningfor congenital heart disease, especially in those fetuses that are going to undergoprenatal surgery. There is currently a high rate of errors in congenital heart diseasescreening, which causes anxiety in parents. This may be due to inadequate imagingtechnique, lack of standardization in the study protocol based on clinical practiceguidelines, or lack of adequate training to perform this type of study. This articlefocuses on the most common errors in screening for congenital heart disease duringsecond trimester morphological ultrasound, based on clinical practice guidelines forfetal echocardiography.